Memajukan Transisi Energi Indonesia: Studi Simulasi Coal to Nuclear (C2N) - Irfan Eko Budiyanto; Sinta Uri El Hakim (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
Indonesia’s ambitious net-zero emissions (NZE) target for 2060 necessitates a transformative shift from coal-dependent power systems to nuclear energy sources. Although previous studies have explored various aspects of energy transitions, limited attention has focused on the possibility of replacing existing coal-fired boilers with nuclear reactors while maintaining the input and output parameters of the current infrastructure. This paper presents an approach to facilitating Indonesia’s nuclear energy transition by a coal-to-nuclear (C2N) simulation study. Specifically, the focus is on the 400 MW coal-fired power plant (CFPP), which relies on coal combustion. This study was designed to model the conversion process of the coal combustion system to a modular nuclear reactor setup while preserving the existing steam turbine and generator infrastructure. The foundation of this study was that the replacement of the nuclear reactor-based heat source must meet the requirements of the pre-existing water and steam cycle design. Various configurations for substituting the current boiler with a nuclear reactor were analyzed in this study, by considering engineering, operational, and modeling aspects. Results from model simulations for nine different operating conditions showed a deviation of the main-steam temperature of about 3% of the design value, starting at 120 MWe and above. Nevertheless, all other parameters of the conversion simulation results demonstrated a very small deviation. The deviation was close to the actual existing operational conditions of the previous CFPP. This paper highlights how the simulation demonstrated a promising integration of legacy infrastructure with emerging nuclear technology.